DISCOURSE ANALYSIS ON SELECTED TEXTS OF BOG BOG BALI CARTOON MAGAZINE - Husnulhotimah; Beny Hamdani; Dian Luthfiyati; Sania Dina Kartika (Journey: Journal of English Language and Pedagogy, 2022)
The recent article intends to describe the application of grammatical cohesive devices on the articles of Bog-Bog Bali Cartoon Magazine and to figure out the effect of grammatical cohesive devices on text to be coherent and unified. The article uses library research with collected from written texts. The data are qualitative data taken from Bog-Bog Bali Cartoon Magazine which were published in 2003. The articles are written texts. The Text is realized by 38 ranks (non-embedded) clauses and 6 ranks shifted (embedded) clauses. There is also cohesion between elements in each text of Bog-Bog Bali Magazine. The use of reference such as personal (e.g., we, us, their, them, it, etc), demonstrative reference (one, the, that, this), comparative reference which shows degree of comparison (e.g., same, finest, most, latest) is often used in the articles. In fact, text one consists of 37 elements of anaphoric reference, 7 elements of cataphoric reference and 7 elements of exophoric reference. . In summary, it reveals that grammatical cohesive can make the text coherent and unified.